What support do people with cirrhosis need from liver healthcare professionals in a liver transplant centre?. Issue 3 (1st September 2016) - Davis, Sarah; Low, Joseph; Greenslade, Lynda; Marshall, Aileen; Thorburn, Doug; Jones, Louise
Abstract : Background and aims: The incidence of liver disease is increasing in the UK; it is now the 3 rd commonest cause of death in those aged under 65. People with cirrhosis often have complex physical problems that require regular comprehensive management. Limited evidence exists on the ways that people with cirrhosis cope with the disease. We aimed to explore their experience to ascertain whether current levels of healthcare support were sufficient. Methods: Ten people with cirrhosis were recruited from hepatology clinics in one liver transplant centre. In semi-structured qualitative interviews, we explored their understanding of their disease and prognosis; healthcare services received; specific problems encountered; concerns for the future. Interviews were audio-taped and transcribed verbatim. Data were analysed using a Framework approach. Results: Our sample was 50% male: 5 were on the liver transplant list. Everyone said that the healthcare they received from the hospital was good; staff continuity and relationships with clinicians were seen as important. However, people lacked understanding of their diagnosis, health status and symptoms and wanted more management advice and psychological support. Contacting a member of the clinical team was difficult if problems developed at home, leading to A+E attendance. Limited discussions were held about disease progression and future care if treatment failed. Conclusions: Symptom burden in people with cirrhosis is high and needs are complex. Active communication from professionals about current disease status and likely progression may enable better understanding and encourage involvement in plans for their future care. References: Poonja Z, Brisebois A, van Zanten SV, et al . Patients with cirrhosis and denied liver transplants rarely receive adequate palliative care or appropriate management. Clin Gastroenterol Hepatol 2014;12 (4):692–698 Kimbell B, Boyd K, Kendall M, Iredale J, Murray SA. Managing uncertainty in advanced liver disease: a qualitative, multi-perspective, serial interview study. BMJ Open 2015;e009241. doi:10.1136/bmjopen-2015-009241